MULHERES RÉS NA COMARCA DE MALLET/PR (1935 - 1995) - BETU, GEOVANA (2021)
The protagonists of this research are women who appear as defendants in criminal cases produced by the County of Mallet from 1935 to 1995. Put in front of the practices, the means of violence and the active posture of these women, we intended to identify and highlight the statements about the women in the condition of defendants in procedural records of various subjects, such as defendants, victims, witnesses, prosecutors and judges. Thus, we have selected 28 criminal cases classified as personal injury, homicide and infanticide. The analysis of these cases possesses a triple theoretical inspiration, namely: concepts related to the study of gender, based on Joan Scott; the contribution of historians specialized in violence, such as Robert Machembled, and Michel Foucault concepts of power, of statements and discourse. In spite of having their lives marked with what was considered a crime, at a given time, the women from Mallet and Paulo Frontin, a rural region of Brazil, were proven capable of defending themselves as well as their children, from being aggressive towards gossipy neighbors in defense of their honor, of consuming alcohol, of having desires like any human being. Women who were protagonists of their lives and in a certain way, broke apart with common sense regarding the usual gender definitions of their time.